1989
DOI: 10.1002/ana.410260604
|View full text |Cite
|
Sign up to set email alerts
|

Isoelectric focusing studies of serum and cerebrospinal fluid in patients with antecedent poliomyelitis

Abstract: The post-poliomyelitis syndrome (PPS) refers to symptoms of new weakness, fatigue, and pain years after recovery from acute poliomyelitis. Oligoclonal IgG bands have been reported in the cerebrospinal fluid (CSF) from PPS patients, suggesting that the syndrome is immune mediated or caused by persistent viral infection. We studied 15 paired serum and CSF samples and 6 unpaired CSF samples from a total of 21 patients with a prior history of poliomyelitis. Quantitative immune studies failed to show evidence for i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0
1

Year Published

1990
1990
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 30 publications
2
6
0
1
Order By: Relevance
“…Furthermore,no poliovirus type-specific IgM antibodies were detected in the CSF or the serum from any of these patients. This is consistent with the results of Dalakas and colleagues [4} and Salazar-Grueso and coworkers [17], who found no evidence for virus persistence by quantitative immune studies of serum and CSF from patients with the postpolio syndrome. Colbere-Garapin and associates 1181 suggested that at least in the absence of an adequate immune defense, poliovirus can induce persistent infections in neuroblastoma cells.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore,no poliovirus type-specific IgM antibodies were detected in the CSF or the serum from any of these patients. This is consistent with the results of Dalakas and colleagues [4} and Salazar-Grueso and coworkers [17], who found no evidence for virus persistence by quantitative immune studies of serum and CSF from patients with the postpolio syndrome. Colbere-Garapin and associates 1181 suggested that at least in the absence of an adequate immune defense, poliovirus can induce persistent infections in neuroblastoma cells.…”
Section: Discussionsupporting
confidence: 93%
“…While not active or having a direct ability to cause PPS symptoms due to restrained RNA synthesis and lack of evidence for direct toxicity, these poliovirus genomic particles have the potential to induce the production of cytokines, such as TNFα, and thereby contribute to gradually worsening chronic inflammation [35]. Other groups have not found evidence for poliovirus persistence [36,37]. This has led to other hypotheses for persistently elevated cytokines to include a poliovirus-induced autoimmune response directed against as of yet unknown neuronal or non-neuronal autoantigens, or an immune response that is completely secondary to CNS damage [10].…”
Section: Discussionmentioning
confidence: 97%
“…14,[53][54][55][56][57] However, several other studies that included evaluation of CSF, skeletal muscle biopsy, and postmortem CNS tissue either did not demonstrate any evidence of poliovirus RNA or a poliovirus-specific immunoglobulin (Ig) M antibody response in patients with strictly defined PPS or demonstrated no association with the laboratory findings and the late functional decline in postpolio patients. [58][59][60][61] Thus, because of the lack of consistent results reported in the research literature, the role of potential poliovirus persistence or reactivation in the pathogenesis of PPS is currently unclear, and, at this point, it does not appear to be the singular cause of this condition.…”
Section: Pathogenesismentioning
confidence: 99%